Inteligencia artificial sostenible y quíntuple hélice: una respuesta ética en el ámbito de la innovación - Terrones Rodríguez, Antonio Luis (2024)
In the Anthropocene and within the context of the Fourth Industrial Revolution, artificial intelligence can be seen as an element that exacerbates the problems related to environmental degradation. Thus, renowned researchers such as Aimee van Wynsberghe and Mark Coeckelbergh have proposed the concept of Sustainable Artificial Intelligence (SAI). However, it is important to connect this conceptual approach with an innovation model that enables its realization for the sake of sustainability. The Quintuple Helix Framework represents an opportunity for boosting SAI through a form of innovation committed to social participation and environmental protection.